Optimizing Moisture and Color: A Comparative Study of Lip Balms Formulated With Raspberry Seed Oil and Coconut Oil - Ku Hasnan, Ku Nur Husna Afifah; Hasni, Noor Afrina; Mohd Sabaruddin , Nurul Najihah; Hashim , Shazana; Rosley, Rozainita (Multidisciplinary Applied Research and Innovation, 2025)
Lip balm is one of the most often used cosmetics to improve the appearance of consumers among a wide range of cosmetics. In this study, organic lip balms were made with raspberry seed oil and coconut oil as the key ingredients using a hot boiled method involving a developed formulation that is effective in moisturizing and protecting the lips using evaluation parameters such as physical appearance, spread ability test, measurement of pH, and moisture analysis. The lip balm was produced with three basic ingredients and two additional ingredients: beetroot coloring for four samples and blueberry coloring for four other samples using raspberry seed oil and coconut oil. Sample H with ratio of raspberry seed oil to beetroot powder of 4:1 was the most effective recipe due to low moisture loss percentage of 0.0331%. Besides, its pH value is measured at 4-5 which corresponds to the skin’s physiological pH.